2022
DOI: 10.1111/eci.13861
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory central BP and arterial stiffness in patients with and without intradialytic hypertension

Abstract: Background Increased arterial stiffness is suggested to be involved in the pathogenesis of intradialytic‐hypertension (IDH). Ambulatory pulse‐wave‐velocity (PWV) is an independent predictor for all‐cause‐mortality in haemodialysis and its prognostic power is better than office PWV. This is the first study examining ambulatory central blood pressure (BP) and arterial stiffness parameters in patients with and without IDH. Methods This study examined 45 patients with IDH (SBP rise ≥10 mmHg from pre‐ to post‐dialy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Ambulatory BP was evaluated with the Mobil-O-Graph device (IEM, Stolberg, Germany), an automated oscillometric ABPM device previously validated for brachial BP measurement according to standard protocols [15] and that was shown to provide same values as a widely used ABPM monitor [16]. Ambulatory pulse wave velocity (PWV) was estimated via mathematical models taking into account the characteristic impedance and age and assuming a 3-element Windkessel model, as described previously [2, 17, 18]. The recording started before a mid-week dialysis session and was programmed to last for a complete standard 48-h intra- and interdialytic period.…”
Section: Methodsmentioning
confidence: 99%
“…Ambulatory BP was evaluated with the Mobil-O-Graph device (IEM, Stolberg, Germany), an automated oscillometric ABPM device previously validated for brachial BP measurement according to standard protocols [15] and that was shown to provide same values as a widely used ABPM monitor [16]. Ambulatory pulse wave velocity (PWV) was estimated via mathematical models taking into account the characteristic impedance and age and assuming a 3-element Windkessel model, as described previously [2, 17, 18]. The recording started before a mid-week dialysis session and was programmed to last for a complete standard 48-h intra- and interdialytic period.…”
Section: Methodsmentioning
confidence: 99%
“…As far as the clinical implications of IDHYPER are concerned, it could relate to impaired ambulatory central BP and pulse wave velocity, which are poor prognostic factors for mortality in HD [30]. Moreover, Shamir et al…”
Section: Clinical Correlates Of Idhypermentioning
confidence: 99%
“…As far as the clinical implications of IDHYPER are concerned, it could relate to impaired ambulatory central BP and pulse wave velocity, which are poor prognostic factors for mortality in HD [30]. Moreover, Shamir et al [23] found that IDHYPER was associated with left ventricular mass index since every 1 mm rise in Δ systolic BP during HD was associated with 0.2 g/m 2 increase in left ventricular mass index in adjusted models.…”
Section: Clinical Correlates Of Idhypermentioning
confidence: 99%